Urban wetlands regulate trace element dynamics at the sediment- water interface - Xiangyu He; Wenming Yan; Xiang Chen; Minjuan Li; Yan Wang; Tingfeng Wu (Environmental Pollution, 2026)

Layered cross-modal fusion for multispectral object detection: A case study on RGB–R walnuts - Huihua Wang; Ruoyu Li; Yuelong Xia; Luhao Fang; Tingfeng Li; Zaiqing Chen; Lijun Yun (Computers and Electronics in Agriculture, 2026)

Identification of a novel major QTL and F-box candidate genes controlling seed dormancy in common wheat - Yuxia Lyu; Yaoyao Zhao; Wenbo Lu; Xu Pan; Wei Gao; Litian Zhang; Huanfeng Wang; Zhaoyu Yu; Ruihan Wang; Tingfeng Shou; Bingbing Tian; Jiajia Cao; et al. (Theoretical and Applied Genetics, 2026)

Emergence of anthropogenic warming in Antarctica - Zihuan Zhang; Sai Wang; Deliang Chen; Tingfeng Dou; Cunde Xiao; Annette Rinke; Shoudong Zhao; Petra Heil; Wen Chen; Minghu Ding (Science Bulletin, 2026)

Amplifying endogenous arsenic flux: The role of sediment bulking driven by organic matter mineralization - Xiangyu He; Wenming Yan; Xiang Chen; Minjuan Li; Yan Wang; Zhongbo Yu; Junliang Jin; Zengchuan Dong; Tingfeng Wu (Water Research, 2026)

Electrochemical oxidation of caprolactam wastewater by a SnO2-Sb electrode with reduced TiO2-xN interlayer:Electrode characterization, environmental impact factors and degradation pathways - Tingfeng Wang; Jun Ma; Zhiqiang Sun; Fang Chang; Zhendong Li; Yingjie Zhao; Wei Ye; Huiting Li (Environmental Research, 2026)

Innovative MnLa-LDH and MnAl-LDH for synergistic multi-mechanism immobilization of internal phosphorus in sediments - Gaoxiang Li; Wenming Yan; Qi Li; Minjuan Li; Junliang Jin; Tingfeng Wu; Chenjun Yang; Yichun Shao; Jingwei Wu; Ningyue Wang (Journal of Environmental Chemical Engineering, 2025)

Behavior of iron and manganese in lanthanum-modified bentonite and calcium peroxide passivated sediments and the coupling effect on cobalt and tungsten - Xiang Chen; Minjuan Li; Xiangyu He; Qi Li; Junliang Jin; Tingfeng Wu; Yichun Shao; Jingwei Wu; Gaoxiang Li; Yan Wang; Wenming Yan (Journal of Environmental Chemical Engineering, 2025)

Seasonal changes-facilitated release of phosphorus and tungsten from the Lake Taihu sediments through reductive dissolution of Fe/Mn (hydr)oxides and competitive adsorption with dissolved organic matter - Xiang Chen; Yan Wang; Minjuan Li; Xiangyu He; Qi Li; Junliang Jin; Tingfeng Wu; Yichun Shao; Jingwei Wu; Gaoxiang Li; Ling Liu; Wenming Yan (Environmental Pollution, 2025)

Uranium release from iron-rich acid soils under IPCC elevated CO2 scenarios: One-sided organic nanocolloidal dominance rather than expected iron oxide colloids - Ziyan Wang; Tingfeng Cheng; Caiqin Wang; Yuwei Zhao; Daoyong Zhang; Xiangliang Pan (Journal of Hazardous Materials, 2025)

Endocrine-driven FGF21 mRNA therapy via route-adaptable lipopolymer nanoparticles for the treatment of pancreatitis - Jia Liu; Ling Zeng; Qian Shen; Tingfeng Yu; Yupeng Ren; Xinxiu Cao; Lingyun Wang; Jinjin Chen (Chemical Engineering Journal, 2025)

RouteView 2.0: A real-time operational planning system for vessels on the Arctic Northeast Passage - Adan Wu; Tao Che; Jinlei Chen; Xiaowen Zhu; Qingchao Xu; Tingfeng Dou; Rui Zhang; Shengpeng Chen; Jiping Wang; Yongfan Guo (Environmental Modelling & Software, 2025)

The transition from macrophyte-dominated to algae-dominated lake systems enhances arsenic release from sediments - Xiangyu He; Wenming Yan; Xiang Chen; Yan Wang; Minjuan Li; Qi Li; Junliang Jin; Zhongbo Yu; Tingfeng Wu (Water Research, 2025)

Inhibition of STRA6 suppresses NSCLC growth via blocking STAT3/SREBP-1c axis-mediated lipogenesis - Yue Zhou; Rong Zhou; Ning Wang; Tingfeng Zhao; Pan Qiu; Chenzi Gao; Meijia Chang; Ning Lin; Xu Zhang; John Zhong Li; Qian Wang (Molecular and Cellular Biochemistry, 2025)

Tungsten migration and transformation characteristics in lake sediments under changing habitats from algae to macrophytes - Xiang Chen; Yan Wang; Lan Zhang; Dongdong Zhu; Wenming Yan; Minjuan Li; Junliang Jin; Tingfeng Wu; Qi Li; Xiangyu He; Gongyao Wu; Yan Tian; et al. (Journal of Hazardous Materials, 2024)

In-situ inhibition mechanism of SO3 formation over MoS2 modified V2O5/TiO2 catalyst within selective catalytic reduction process - Tingfeng Shan; Zhen Zhang; Bowen Li; Qi Zhang; Xiangfu Wang; Yusi He; Hongmin Yang (Fuel, 2024)

Underwater Gyros Denoising Net (UGDN): A Learning-Based Gyros Denoising Method for Underwater Navigation - Chun Cao; Can Wang; Shaoping Zhao; Tingfeng Tan; Liang Zhao; Feihu Zhang (Journal of Marine Science and Engineering, 2024)
Autonomous Underwater Vehicles (AUVs) are widely used for hydrological monitoring, underwater exploration, and geological surveys. However, AUVs face limitations in underwater navigation due to the high costs associated with Strapdown Inertial Navigation System (SINS) and Doppler Velocity Log (DVL), hindering the development of low-cost vehicles. Micro Electro Mechanical System Inertial Measurement Units (MEMS IMUs) are widely used in industry due to their low cost and can output acceleration and angular velocity, making them suitable as an Attitude Heading Reference System (AHRS) for low-cost vehicles. However, poorly calibrated MEMS IMUs provide an inaccurate angular velocity, leading to rapid drift in orientation. In underwater environments where AUVs cannot use GPS for position correction, this drift can have severe consequences. To address this issue, this paper proposes Underwater Gyros Denoising Net (UGDN), a method based on dilated convolutions and LSTM that learns and extracts the spatiotemporal features of IMU sequences to dynamically compensate for the gyroscope’s angular velocity measurements, reducing attitude and heading errors. In the experimental section of this paper, we deployed this method on a dataset collected from field trials and achieved significant results. The experimental results show that the accuracy of MEMS IMU data denoised by UGDN approaches that of fiber-optic SINS, and when integrated with DVL, it can serve as a low-cost underwater navigation solution.

Characteristics of methane and carbon dioxide in ice caves at a high-mountain glacier of China - Zhiheng Du; Hao Cui; Lei Wang; Fangping Yan; Yushuo Liu; Qian Xu; Simin Xie; Tingfeng Dou; Yanzhao Li; Pengfei Liu; Xiang Qin; Cunde Xiao (Science of The Total Environment, 2024)

Arsenic distribution characteristics and release mechanisms in aquaculture lake sediments - Xiangyu He; Wenming Yan; Xiang Chen; Yan Wang; Minjuan Li; Qi Li; Zhongbo Yu; Tingfeng Wu; Chengmei Luan; Yichun Shao; Jingwei Wu (Journal of Hazardous Materials, 2024)

Side-Scan Sonar Image Generator Based on Diffusion Models for Autonomous Underwater Vehicles - Feihu Zhang; Xujia Hou; Zewen Wang; Chensheng Cheng; Tingfeng Tan (Journal of Marine Science and Engineering, 2024)
In the field of underwater perception and detection, side-scan sonar (SSS) plays an indispensable role. However, the imaging mechanism of SSS results in slow information acquisition and high complexity, significantly hindering the advancement of downstream data-driven applications. To address this challenge, we designed an SSS image generator based on diffusion models. We developed a data collection system based on Autonomous Underwater Vehicles (AUVs) to achieve stable and rich data collection. For the process of converting acoustic signals into image signals, we established an image compensation method based on nonlinear gain enhancement to ensure the reliability of remote signals. On this basis, we developed the first controllable category SSS image generation algorithm, which can generate specified data for five categories, demonstrating outstanding performance in terms of the Fréchet Inception Distance (FID) and the Inception Score (IS). We further evaluated our image generator in the task of SSS object detection, and our cross-validation experiments showed that the generated images contributed to an average accuracy improvement of approximately 10% in object detection. The experimental results validate the effectiveness of the proposed SSS image generator in generating highly similar sonar images and enhancing detection accuracy, effectively addressing the issue of data scarcity.

Underwater Mapping and Optimization Based on Multibeam Echo Sounders - Feihu Zhang; Tingfeng Tan; Xujia Hou; Liang Zhao; Chun Cao; Zewen Wang (Journal of Marine Science and Engineering, 2024)
Multibeam echo sounders (MBESs) enable extensive underwater environment exploration. However, due to weak correlation between adjacent multibeam sonar data and difficulties in inter-frame feature matching, the resulting underwater mapping accuracy frequently falls short of the desired level. To address this issue, this study presents the development of a multibeam data processing system, which includes functionalities for sonar parameter configuration, data storage, and point cloud conversion. Subsequently, an Iterative Extended Kalman Filter (iEKF) algorithm is employed for odometry estimation, facilitating the initial construction of the point cloud map. To further enhance mapping accuracy, we utilize the Generalized Iterative Closest Point (GICP) algorithm for point cloud registration, effectively merging point cloud data collected at different times from the same location. Finally, real-world lake experiments demonstrate that our method achieves an Absolute Trajectory Error (ATE) of 15.10 m and an average local point cloud registration error of 0.97 m. Furthermore, we conduct measurements on various types of artificial targets. The experimental results indicate that the average location error of the targets calculated by our method is 4.62 m, which meets the accuracy requirements for underwater target exploration.

Distinct and shared endothermic strategies in the heat producing tissues of tuna and other teleosts - Baosheng Wu; Xueli Gao; Mingling Hu; Jing Hu; Tianming Lan; Tingfeng Xue; Wenjie Xu; Chenglong Zhu; Yuan Yuan; Jiangmin Zheng; Tao Qin; Peidong Xin; et al. (Science China Life Sciences, 2023)

Urine 2-hydroxyphenanthrene is associated with current asthma: evidence from NHANES 2007–2012 - Lingyi Lu; Tingfeng Mao; Rui Xu; Lanxia Liu; Jiefeng Qian; Kai Yang; Anjie Yuan; Xinyue Wang; Rong Ni (International Archives of Occupational and Environmental Health, 2023)

Alkalization-induced disintegration increased redox activity of solid humic acids and its soil biogeochemical implications - Caiqin Wang; Shuting Tang; Hangzhe Chen; Tingfeng Cheng; Daoyong Zhang; Xiangliang Pan (Science of The Total Environment, 2023)

3D-imaging and quantitative assessment for size-related penetration of HfO2 nanoparticles in breast cancer tumor by synchrotron radiation microcomputed tomography - Jiali Wang; Tingfeng Zhang; You Liao; Wei Chen; Shanshan Liang; Si Xu; Hao Fang; Meng Wang; Lingna Zheng; Zhanjun Gu; Zhiyong Zhang; Bing Wang; et al. (Analytica Chimica Acta, 2023)

Electrochemical properties of humic acid and its novel applications: A tip of the iceberg - Caiqin Wang; Tingfeng Cheng; Daoyong Zhang; Xiangliang Pan (Science of The Total Environment, 2023)

Protective-mechanism-exclusive thermal stability modes of soil organic matter: Novel implication for wildfire effect on soil organic carbon - Caiqin Wang; Tingfeng Cheng; Shuting Tang; Mengxuan Li; Daoyong Zhang; Xiangliang Pan (Science of The Total Environment, 2023)

Affinity-based alleviation of dissolved organic matter (DOM) on tetracycline toxicity to photosynthesis of green algae Chlorella vulgaris: roles of hydrophilic and hydrophobic DOM - Caiqin Wang; Hang Xu; Tingfeng Cheng; Shuting Tang; Daoyong Zhang; Meichao Li; Xiangliang Pan (Environmental Science and Pollution Research, 2023)

On the drivers of temperature extremes on the Antarctic Peninsula during austral summer - Sai Wang; Minghu Ding; Ge Liu; Ting Wei; Wenqian Zhang; Wen Chen; Tingfeng Dou; Cunde Xiao (Climate Dynamics, 2022)

Exploring and quantifying the relationship between instantaneous wind speed and turbidity in a large shallow lake: case study of Lake Taihu in China - Wenhao Ding; Jinxiao Zhao; Boqiang Qin; Tingfeng Wu; Senlin Zhu; Yun Li; Shikai Xu; Shiping Ruan; Yong Wang (Environmental Science and Pollution Research, 2021)

Mechanism of phosphorus mobility in sediments with larval (Propsilocerus akamusi) bioturbation - Wenming Yan; Musong Chen; Ling Liu; Tingfeng Wu; Yi Zhang; Han Wang; Xigang Xing; Kongming Fan (Environmental Science and Pollution Research, 2020)

Features and impacts of currents and waves on sediment resuspension in a large shallow lake in China - Wenhao Ding; Tingfeng Wu; Boqiang Qin; Yingtien Lin; Han Wang (Environmental Science and Pollution Research, 2018)

QTL underlying field grain drying rate after physiological maturity in maize (Zea Mays L.) - Zhenhua Wang; Xia Wang; Lin Zhang; Xianjun Liu; Hong Di; Tingfeng Li; Xiaochun Jin (Euphytica, 2012)